2022
DOI: 10.3389/fphar.2022.873614
|View full text |Cite
|
Sign up to set email alerts
|

ELA-11 protects the heart against oxidative stress injury induced apoptosis through ERK/MAPK and PI3K/AKT signaling pathways

Abstract: Increasing evidence revealed that apoptosis and oxidative stress injury were associated with the pathophysiology of doxorubicin (DOX)-induced myocardial injury. ELABELA (ELA) is a newly identified peptide with 32 amino acids, can reduce hypertension with exogenous infusion. However, the effect of 11-residue furn-cleaved fragment (ELA-11) is still unclear. We first administrated ELA-11 in DOX-injured mice and measured the cardiac function and investigated the effect of ELA-11 in vivo. We found that ELA-11 allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…They exhibited inotropic activities both in vitro and in animal disease models (25). Wang et al (42) found that ELA-11 alleviated heart injury induced by DOX and inhibited cardiac tissues from apoptosis. In vitro , ELA-11 regulated the sensitivity toward apoptosis induced by oxidative stress with DOX treatment through PI3K/AKT and ERK/MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…They exhibited inotropic activities both in vitro and in animal disease models (25). Wang et al (42) found that ELA-11 alleviated heart injury induced by DOX and inhibited cardiac tissues from apoptosis. In vitro , ELA-11 regulated the sensitivity toward apoptosis induced by oxidative stress with DOX treatment through PI3K/AKT and ERK/MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As for the involved pathways, several articles reported that APJ ligands exert cardioprotection against I/R mainly triggering PI3K-Akt-NO and MEK 1/2-ERK1/2 signalling pathways [ 85 , 88 , 89 , 90 , 91 , 92 , 93 ].…”
Section: Cardioprotective Role Of Apj Endogenous Ligandsmentioning
confidence: 99%
“…Only a few studies investigated the cardioprotective role of ELA [ 85 , 92 , 97 , 100 ], though its effectiveness against I/R injury was confirmed in other organs, such as kidney, brain, and lung [ 110 , 111 , 112 , 113 ].…”
Section: Cardioprotective Role Of Apj Endogenous Ligandsmentioning
confidence: 99%